2016
DOI: 10.18632/oncotarget.8884
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein amplifies TGF-β promotion on HCC motility through down-regulating PPM1a

Abstract: Over-activation of transforming growth factor-β (TGF-β) signaling pathway promotes cell migration and invasion in hepatocellular carcinoma (HCC). The Hepatitis B virus X protein (HBx) is involved in the enhancement of TGF-β signaling pathway in HCC while the mechanism remains unclear. Protein phosphatase magnesium dependent 1A (PPM1a) functions as a phosphatase essential for terminating the TGF-β signaling pathway by dephosphorylating p-Smad2/3. In this study, we found that HBx dose-dependently downregulated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Previous studies have reported functional crosstalk between HBx and TGF-β1 in HBV pathogenesis. For example, HBx transactivated the TGF-β1 promoter [21], interacted with Smad4 [39], and downregulated PPM1a [40], thereby amplifying TGF-β1 signaling. HBx shifted hepatocytic TGF-β1 signaling from tumor suppression to oncogenesis in the early carcinogenic process [22], and the TGF-β1 pathway may be involved in the accelerated tumor development of HBx transgenic mice after partial hepatectomy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported functional crosstalk between HBx and TGF-β1 in HBV pathogenesis. For example, HBx transactivated the TGF-β1 promoter [21], interacted with Smad4 [39], and downregulated PPM1a [40], thereby amplifying TGF-β1 signaling. HBx shifted hepatocytic TGF-β1 signaling from tumor suppression to oncogenesis in the early carcinogenic process [22], and the TGF-β1 pathway may be involved in the accelerated tumor development of HBx transgenic mice after partial hepatectomy [30].…”
Section: Discussionmentioning
confidence: 99%
“…39,40 HBV chronic infection is currently estimated to influence almost 240 million people, globally, of which approximately 10% have an increased risk of developing cirrhosis and HCC. 4,41 Similar to HCV, HBV also interacts with the TGF-β pathway, a phenomenon mainly mediated by HBV X protein (HBx), which may exert diverse effects on the pathogenesis of the HBV-mediated liver pathologies 7,21,42,43 (Figure 3). Evidence by Murata further supported the hypothesis that the TGF-β pathway is directly involved in liver tumorigenesis, where HBx was shown to switch the target of hepatocytic TGF-β signaling from the TGFbRI/ pSmad3C/p21 anti-tumor pathway to the JNK/pSmad3L/c-Myc tumor supportive pathway in the early stages of liver carcinogenesis.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…7,21,44 In this respect, Liu suggested a new mechanism underlying the pathogenesis of HBV-caused HCC; HBx downmodulates protein phosphatase magnesium-dependent 1A (PPM1a) levels, resulting in overactivation of the TGF-β signaling pathway. 7 In fact, HBx was shown to promote the degradation of PPM1a, a p-Smad2/3 phosphatase required for terminating TGF-β signaling, through elevating its ubiquitination. Furthermore, Yoo showed HBx upregulates TGF-β expression by acting through the Egr transcription factors binding site.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
See 2 more Smart Citations